Interleukin-1 beta and Interleukin-6 Expression and Gene Polymorphisms in Subjects with Peri-Implant Disease - Melo, Rafaela F. [UNESP]; Lopes, Beatriz M. V. [UNESP]; Shibli, Jamil A.; Marcantonio Júnior, Elcio [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Thompson Galli, Gloria M. [UNESP] (Wiley-Blackwell, 2012)
Background: Polymorphisms found in the IL-1 family genes have been associated with susceptibility of periodontal disease. However, very little is known about the relationship between polymorphisms on inflammatory mediators' genes and peri-implant disease.Purpose: The aim of the present study was to evaluate interleukin-1 beta (IL-1 beta) and interleukin-6 (IL-6) concentration in the crevicular fluid, and the impact of gene polymorphisms on healthy and diseased implants in comparison with healthy teeth.Materials and Methods: We examined 47 implants and teeth in 47 patients grouped as: 31 healthy implants, 16 implants with peri-implantitis, 31 healthy teeth from patients with healthy implants, and 16 healthy teeth from patients with peri-implantitis. Clinical parameters were recorded from all implants and teeth. Gingival crevicular fluid was collected to evaluate the concentration of IL-1 beta and IL-6. Cells from buccal mucosa were collected and their genomic DNA extracted for identification of the following polymorphisms: IL1B+3954, IL1B-511, and IL6-174.Results: Clinical evaluation demonstrated that implants with peri-implantitis had less favorable indexes for probing depth (PD), relative clinical attachment level (CAL), bleeding on probing, and suppuration when compared with healthy implants and, for PD and CAL when compared with healthy teeth. There was no significant difference in the concentration of IL-1 beta and IL-6 detected between groups. There were no statistically significant differences between alleles and polymorphisms distribution on the studied population.Conclusions: There was no correlation between the concentration of IL-1 beta and IL-6 in the crevicular sulcular fluid present in healthy or diseased osseointegrated implants in comparison with healthy teeth. The studied gene polymorphisms had no influence on peri-implant disease.
Keywords: genetic; gingival crevicular fluid; implant; interleukin-1; interleukin-6; polymorphism